Systematic approach to training for nuclear facility personnel : processes, methodology and practices. (IAEA nuclear energy series, 2021)
"Training is an important tool to achieve and maintain the required competence of personnel working in nuclear facilities. Effective training and qualification of personnel are necessary for the achievement of high safety and efficiency standards in nuclear facility performance. Training and qualification combined is a key feature of the integrated management systems of nuclear facilities. It is these considerations that led to this publication which consolidates the experience gained worldwide using the systematic approach to training (SAT) for nuclear facility personnel. It provides a basis for establishing and sustaining the quality and reliability of training and qualification for all main categories of nuclear facility personnel. SAT has proved its effectiveness in nuclear and other safety critical industries over decades and is recognized as the best international practice in nuclear training. The publication details the processes and methodology, presents good practices and offers recommendations from the experts in the field on the entire set of activities within the SAT-based training methodology and provides examples of SAT application. It builds on, and supersedes, guidance provided in an earlier IAEA publication (Technical Report Series 380, Nuclear Power Plant Personnel Training and its Evaluation: A Guidebook). A key feature of this publication is demonstrating how SAT-based training serves as one of the important processes in a nuclear facility management system and how it integrates with other processes."--Publisher's description.